Compact wideband lumped balun with out‐of‐band suppression using tail inductor. Issue 19 (1st September 2013) - Ye, Yu; Li, Lingyun; Gu, Jianzhong; Sun, Xiaowei
Abstract : A novel compact 2.45 GHz wideband lumped balun with out‐of‐band suppression using a tail inductor has been proposed. By adding an extra transmission zero in even‐mode around operation frequency, the tail inductor can improve phase balanced performance and enlarge operational bandwidth of the balun. Besides, the tail inductor together with a band‐stop resonator can realise out‐of‐band transmission zero in even‐mode. The measured results illustrate a relative 41% bandwidth, namely from 2.35 to 3.35 GHz. Over the operation frequency, a less than 0.5 dB amplitude imbalance and a less than ± 7° phase error have been demonstrated. The out‐of‐band suppressions of two output ports at 5.3 GHz are 24.5 and 27.5 dB, respectively.